FINANCING OF INVESTMENT PROJECTS OF INNOVATIVE TYPE: METHODS, SOURCES - Abzhalelov S. R.,; Celebi A. D.,; Lailieva E. D., (Academic Journal of Physical and Chemical Sciences, 2020)
It is shown that countries can provide high rates of economic growth in the production of high-tech products with high added value. The transition to an innovative economy with a developed business requires significant investment in education and science, the development of new products. The most effective methods of financing innovative projects and domestic enterprises are: own funds of enterprises, joint-stock financing, bank loans and venture financing, raising funds by placing shares and bonds, leasing. The advantages and disadvantages of each type of funding sources are noted. The initial stage of financing an innovative firm combines its own and attracted funds from venture investors (entrepreneurs) and the venture fund to finance research, develop new products, and launch production. The second stage of financing includes evaluation of the project idea, market research, and comparison of market needs with the company's production capabilities. After passing the second stage, it starts production, which is carried out at the expense of entrepreneurs and internal investors, after which it enters the market and regulates the permanent access system.